Efficient distributed traffic offloading algorithm based on SDN architecture - Wen-jie QIAN; Zhu REN; Wei-wei CHENG; Wen-tao LYU; Wei-qiang XU (Tongxin xuebao)
For addressing the problem of mobile data traffic offloading,network service cost minimization problem model was proposed,which considered the cost of base stations and the consumption of access points under the SDN architecture.Due to the defects of convergence speed and privacy security in the traffic offloading algorithm based on dual decomposition,the traffic offloading algorithm based on proximal Jacobian ADMM was proposed and an implementation scheme to ensure the privacy and security was designed.Meanwhile,the simulation results show that the algorithm based on the proximal Jacobian ADMM is superior to the dual decomposition algorithm in terms of convergence speed.